2009
DOI: 10.1177/1753193409105189
|View full text |Cite
|
Sign up to set email alerts
|

Undisplaced scaphoid waist fractures: is 4 weeks’ immobilisation in a below-elbow cast sufficient if a week 4 CT scan suggests fracture union?

Abstract: This prospective study investigated a cohort of 59 scaphoid waist fractures which were treated nonoperatively in a below-elbow plaster cast for 4 weeks and then underwent a Week 4 CT scan to assess displacement and progress to union. Forty-three were classed as undisplaced and 37 of these 43 were also classed as 'united'. All the 37 undisplaced and 'united' fractures united with up to 8 weeks' cast immobilisation, including 26 which were taken out of plaster at 4 weeks and mobilised. We conclude that scaphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 16 publications
0
43
0
1
Order By: Relevance
“…suggested that below elbow cast immobilization for as little as four weeks may be sufficient treatment for undisplaced fractures, with 86% of patients showing fracture union on CT at four weeks. In this study, the majority of these patients (67%) had cast removed at four weeks and all fractures achieved union 23 . Rhemrev et al .…”
Section: Treatment Options and Outcomesmentioning
confidence: 56%
“…suggested that below elbow cast immobilization for as little as four weeks may be sufficient treatment for undisplaced fractures, with 86% of patients showing fracture union on CT at four weeks. In this study, the majority of these patients (67%) had cast removed at four weeks and all fractures achieved union 23 . Rhemrev et al .…”
Section: Treatment Options and Outcomesmentioning
confidence: 56%
“…Geoghegan et al report success following 4 weeks of immobilization for undisplaced scaphoid waist fractures that have evidence of union or partial union on the CT scan at week 4 [18]. When clinical decisions are based on X-rays only, this may lead to prolonged, unnecessary immobilization or an unnecessary push towards surgery [18]. By determining the percentage of union for scaphoid fractures based on CT scan, we can more accurately follow these fractures as they progress through the phases of healing.…”
Section: Discussionmentioning
confidence: 99%
“…If these show the fracture is undisplaced and appears to have united across 50 % of its cross section, then the fracture has almost certainly united suffi ciently to discard the cast and mobilise the wrist [ 31 ].…”
Section: Assessment Of Fracture Unionmentioning
confidence: 98%